2017
DOI: 10.18869/acadpub.jafm.73.242.27352
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Separation Control Using Vortex Generator and Slot Jet in a High Load Compressor Cascade

Abstract: The compressor cascade performance is significantly restricted by the secondary flow mainly presented as the trailing edge separation and corner stall. This paper develops a synthetic flow control approach in a high turning cascade using the vortex generator and slot jet approach. Numerical simulations were conducted to assess the flow control benefits and illustrate the flow control mechanisms. Four configurations, the baseline, the two individual approaches and the synthetic approach, were simulated to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Additionally, the occurrence of softer peaks in θ and ω curves for 28.93°in Figures 8 and 9 confirms a statement that the separation zone is too large to be removed by slot treatment-as stated before. 20,32 When comparing the performance criteria of the slotted profile of IG-25 with the baseline profile at two higher levels of the angle of attack, it shows not only a better performance under the same operating angle but also in comparison with the baseline profile in the design condition.…”
Section: Optimum Slot Location (X Opt )mentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, the occurrence of softer peaks in θ and ω curves for 28.93°in Figures 8 and 9 confirms a statement that the separation zone is too large to be removed by slot treatment-as stated before. 20,32 When comparing the performance criteria of the slotted profile of IG-25 with the baseline profile at two higher levels of the angle of attack, it shows not only a better performance under the same operating angle but also in comparison with the baseline profile in the design condition.…”
Section: Optimum Slot Location (X Opt )mentioning
confidence: 99%
“…An analysis of the flow field will identify any secondary flow patterns; with the aid of numerical limiting streamlines and flow patterns (topology) near surfaces, complex rotating vortices and the mechanisms of their development along the passage will be revealed. Similar studies have used this approach for either topological investigation of the flow pattern near end walls 1,3,20,21 or as a strategy to enhance the flow control methods. 7,30,40 Figure 10 presents limiting streamlines on the vertical section of the blade near the end wall for both the slotted and baseline profiles at an angle of attack of 28.93°.…”
Section: -2-flow Field Analysis and Slot Arrangementmentioning
confidence: 99%
See 2 more Smart Citations
“…The jet flow can decrease thickness of the boundary layer on suction surface and delay the onset of flow separation. 7 The slotted blade was firstly proposed by Rockenbach, 8 whose experimental results showed that mid-span flow structure of the rotor blade was improved but the method made a poor effect at endwall region. An experimental investigation of a highly-loaded compressor cascade with a full-span slot was studied by Hu et al 9 The results showed that total pressure loss of the cascade was reduced by 21.9%, average flow turning angle was increased by 2.1 , and range of the incidence angle was widened by 3 at least.…”
Section: Introductionmentioning
confidence: 99%